Prediction of Dynamic Coefficients of Bump-Type Foil Bearings with Bumps Considered as Link-Spring Structures - Kai Feng; Shigehiko Kaneko (Tribology Online, 2011)
Bump-type foil bearings have demonstrated excellent performance in service experiences in recent 30 years. Due to their special structures, the performance prediction models must couple the air pressure with the elastic deflection of the compliant foil structure. The solution of air pressure has been well settled in the hydrodynamic lubrication theory, while the deflection of foils now still cannot be accurately solved due to the mechanical complexity of the corrugated bump structure. A theoretical model, link-spring model, was developed to predict the structure characteristics of foil strips in a previous work. Effects of four factors, i.e., the elasticity of the bump foil, the interaction forces between bumps, the friction forces at contact surfaces, and the local deflection in the top foil, had been taken into consideration. In this investigation, based on the link-spring model, a perturbation approach is used to determine the dynamic characteristics of bump-type foil bearings. The calculations have been performed with different meshes. And the accordant results show that the calculation is independent on the mesh. The effects on the dynamic coefficients of the friction forces and radial clearance are also evaluated using the perturbation method.